Sharia Fintech In The Digital Age: Human Rights in Sharia Fintech Through Criminal Law Safeguards - Sawitri Yuli Hartati; Emelia Kontesa; Agri Baskara (Universitas Negeri Semarang, 2023)
This research analyses the impact of Sharia fintech development on human rights in the Industrial Revolution 4.0 and Society 5.0. In this digital era, technological developments have brought a significant revolution in the financial sector, including within the scope of sharia finance. This study aims to analyze the impact of the expansion of sharia fintech on human rights in a broader context. This research uses a normative legal method by adopting a statutory, conceptual, comparative and futuristic approach. By using analytical content, this study explores the impact generated by implementing sharia fintech on aspects related to human rights, including financial inclusion, social justice, and economic opportunities. The analysis shows that sharia fintech, operating with Islamic economic principles emphasizing fairness, sustainability, and risk sharing, can contribute to fulfilling and protecting human rights. Along with the benefits offered, such as increasing access to financial services for the public, potential challenges and obstacles are also considered, including data privacy and cyber security issues. The results of this study Research shows that Islamic FinTech in Indonesia has great potential to improve financial inclusion and economic justice, especially for marginalised groups. However, challenges such as limited awareness, immature regulations, and security concerns need to be addressed through supportive regulations, public education, and collaboration with Islamic financial institutions. The importance of balancing technological innovation, sharia ethics, and legal protection is reflected in the implementation of various laws in Indonesia, such as the Criminal Code, ITE Law, and Personal Data Protection Law, to regulate electronic transactions, protect personal data, and prevent financial crimes.